An efficient and sustainable furfurylamine production from biomass-derived furfural by a robust mutant ω-transaminase biocatalyst. (February 2023) - Di, Junhua; Li, Qing; Ma, Cuiluan; He, Yu-Cai
Graphical abstract: Highlights: Two amino acid residues of Aspergillus terreus ω-transaminase was mutated. The transamination activity and thermostability of TMEF were significantly improved. Furfural (500 mM) was transformed to furfurylamine (92% yield) with TMEF after 12 h. 101.3 mM of biomass-derived furfural were fully converted to furfurylamine in 5 h. An efficient chemoenzymatic catalysis of biomass to valuable furans was developed. Abstract: Furfurylamine is a key furan-based compound for manufacturing perfumes, fibers, additives, medicines and agrochemicals. It can be obtained by amination of furfural by ω-transaminase ( At AT) from Aspergillus terreus . In this work, site-directed mutant of amino acid residues [Threonine (T) at AT130 was mutated to Methionine (M) and Glutamic acid (E) at AT133 was mutated to Phenylalanine (F)] was used to change in the flexible region of At AT. The transamination activity and thermostability were significantly improved. In ChCl:MA (30 wt%), furfural (500 mM) was efficiently transformed into furfurylamine (92% yield) with TMEF after 12 h. 101.3 mM of biomass-derived furfural and 129.7 mM of D -xylose-derived furfural were wholly converted into furfurylamine within 5 h, achieving the productivity of 0.465 g furfurylamine/(g xylan in corncob) and 0.302 g furfurylamine/(g D -xylose). This established chemoenzymatic conversion strategy by bridging chemocatalysis and biocatalysis could be utilized in the valorisation of renewable biomass to valuable furans.